Pengaruh Edukasi D3 Pada Ibu Postpartum Di Klinik Bersalin Aminah Amin Samarinda - Stephanie Sorta Llyod; Eva purwaningsih; Siti Noorbaya (Universitas Ngudi waluyo, 2020)
Postpartum depression is depression experienced by mothers during childbirth which begins with fatigue, rest or sleep disturbances, a feeling of not being able to take care of their babies, a feeling of excessive joy due to a baby being born and stress symptoms. One of the efforts to reduce it is educational intervention for early detection of postpartum depression (D3). This study used a Quasi Experiment with a pre and posttest approach with control group. Researchers used an untreated control group as a comparison to determine whether the differences in postpartum depression in the intervention group with the control group were caused by the treatment given D3 intervention. The population in this study were all 110 mothers who had given birth at Aminah Amin's Maternity Clinic. The sample of this study was 60 respondents respectively 30 control group respondents and 30 treatment group respondents. The results showed that there were 48.4% of mothers suffering from postpartum depression after the D3 education intervention there was a decrease in postpartum depression by 65%. The result of the Pair-Test test shows that there is a difference in postpartum depression in mothers with D3 educational interventions with mothers who are not given D3 educational interventions with a sig.0.011 (pË‚0.05) value and based on the Logistic Regression Test shows there is no relationship between age and work towards depression. postpartum and there was a significant influence on maternal education (p = 0.003), maternal parity (p = 0.016) and husband support (p = 0.000) on postpartum depression. The need to increase health education for postpartum mothers and provide education on early detection of depression (D3) to husbands and families as companions for the mother during childbirth until the postpartum period